"Inflammatory Bowel Disease—Not Just the Bowel's Bane": Peripheral Arterial and Venous Thrombosis in a Patient With Crohn Disease. (October 2020) - Boussi, Leora; Safaya, Aditya; Goyal, Arun; Mateo, Romeo; Laskowski, Igor; Babu, Sateesh
Introduction: Inflammatory bowel disease (IBD) is a chronic multisystem inflammatory condition with associated endothelial dysfunction and dysregulated coagulation. Although deep venous thrombosis (DVT) in IBD has been well described, arterial thrombosis and thromboembolism are less commonly appreciated. Methods: A 63-year-old male with a known history of Crohn disease presented with acute-onset right arm pain. His past vascular history was significant for left lower extremity DVT with an existing inferior vena cava filter and acute ischemia of the right lower extremity requiring a below-knee amputation a year ago. Imaging revealed acute brachial, ulnar, and radial artery thrombosis. Results: Patient underwent an open right brachial, radial, and ulnar thrombectomy to restore vascular flow. He required multiple exploration and thrombectomy for reocclusion of the vessels in the early postoperative period. He later developed a rapidly deteriorating clinical status, flank ecchymosis and swelling concerning for soft tissue ischemia, and compartment syndrome heralding an eventual hemodynamic collapse. On exploration, he was found to have chronic fibrosis of his left femoral vein and femoral artery occlusion. Clinically, the patient deteriorated rapidly, which resulted in his demise. Conclusion: The inflammatory reaction in IBD leads to arterial stiffening and hypercoagulability, which should theoretically increase the risk for vascular disease. Although the link between IBD and DVT is well established, arterial thrombosis and thromboembolism remain widely debated, with some implications for therapeutic intervention. The link between vascular thrombosis and IBD must be examined further, as the treatment and prevention of vascular complications in IBD depends on our understanding of this relationship.